Flexibility study on a dual mode natural gas plant in operation - Díaz, María Soledad (2002)
This work addresses a flexibility study on a natural gas processing plant through the integration of a process simulator to a "worst case" flexibility strategy. The plant has a gas subcooled turboexpansion design, which is suitable for working in dual operation mode; i.e., in either ethane production or ethane rejection mode. The selected uncertain parameters (feed flowrate, condensable hydrocarbons content, carbon dioxide content, and ambient temperature) have great impact on process operating conditions. The use of the worse case algorithm with the KS overestimation function for inequality constraints has also been explored to improve computational time, and numerical results are compared for both solution strategies. Results show, in terms of both robustness and speed of computation, that this approach can be a useful tool to complement operational analysis of large processing units, commonly performed by simulation and "what if" studies.